An Engineering Method for Predicting Induced Stress and Deformation in Secondary Shot Peening - CHEN Li-xue, LI Wei-gang, JIANG Jian-Jun, WANG Cheng-yu, MEN Xiang-nan, CHAO Xin, ZENG Wei-kui, YANG Jie (Cailiao Baohu)
For establishing an equivalent analysis method of secondary shot peening, under the conditions that the induced stress and the saturation of single shot peening are known, the engineering prediction of induced stress and deformation of secondary shot peening of metal parts were carried out.Based on the saturation curve of single shot peening, the change rule of secondary shot peening saturation with shot peening time was discussed.The peening induced stress was expressed in the form of sine function, and the relationship between the average induced stress and saturation of the parts was established.Result showed that aiming at the secondary shot peening process with different sizes, the finite element simulation based on multi shot random shot peening technology was carried out, and the difference between the shot peening induced stress and the theoretical result was about 5%; aiming at the secondary shot peening process with different shot peening pressure, the standard Almen test piece was used for shot peening test, and the difference between the deformation of the test piece and the theoretical result was about 3%.In general, the results of simulation and experiment verified the validity and accuracy of the proposed prediction method, and the residual stress and deformation of the parts after secondary shot peening could be predicted.